PELATIHAN PELAKU UMKM BERBASIS DIGITAL UNTUK MENINGKATKAN EFEKTIVITAS DAN EFISIENSI PROSES BISNIS DI KECAMATAN BATANGAN KAB. PATI - Teguh Setiadi; Robby Andika Kusumajaya; Bagus Sudirman; Priyadi Priyadi; Eka Satria Wibawa (Jurnal Padamu Negeri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the regional economy, including in Batangan District, Pati Regency. However, most MSMEs still face challenges such as low digital literacy, limited technology utilization, and poorly organized financial records. These conditions impact the low effectiveness and efficiency of MSME business processes. This community service activity aims to improve the effectiveness and efficiency of MSME business processes through digital-based training for MSME actors. The activity implementation method uses a participatory and applied approach that includes preparation, training, and mentoring stages. The target of the activity is micro and small-scale MSME actors in Batangan District, Pati Regency. The training material focused on digital marketing through social media and marketplaces, as well as financial records based on simple applications. Evaluation of the activity was carried out through pre- and post-tests, observations, and discussions with participants. The results of the activity showed an increase in understanding of digital literacy, the use of digital media in marketing, and the regularity of business financial records. The application of digital technology has a positive impact on increasing marketing effectiveness and business management efficiency. Thus, digital-based training has proven effective in supporting MSME empowerment and strengthening the local economy in Batangan District, Pati Regency.